ANALISIS USAHA PENANGKARAN BENIH PADI BERSERTIFIKAT KELOMPOK TANI HARAPAN JAYA DESA TEGAL REJO BELITANG OKU TIMUR - Munsiarum (Jurnal Bakti Agribisnis, 2019)
The purpose of this study was to calculate the amount of income and financial feasibility of the Harapan Jaya Farmer Group's Certified Rice Seed Breeding Business, Tegal Rejo Belitang Village, OKU Timur. The research was conducted in Tegal Rejo Village, Belitang District, East OKU Regency. The location selection was carried out purposively, namely in the village of Tegal Rejo and was carried out in March 2019. This research was conducted using a survey method. Sampling was carried out by using the census method for all populations, namely KT Harapan Jaya, which operates a certified rice seed breeding business in Tegal Rejo Village. The results showed that the total production cost incurred by certified rice seed producers in Tegal Rejo Village was IDR 652,183,535, business revenues amounted to IDR 714,308,000 so that the income received was IDR 62,124,465. The certified rice seed breeding business in Tegal Rejo Village is financially feasible to be developed, this can be seen from the calculation of the NPV value of the business of IDR 32,618,185, the IRR value is 76.93% and the Net B / C value is 1, 68.